2015
DOI: 10.1161/strokeaha.115.011269
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and Clinical Predictors of Recurrent Ischemia in Symptomatic Internal Carotid Artery Occlusion

Abstract: Background and Purpose-Occlusion of the internal carotid artery puts patients at risk of recurrent ischemic events because of hemodynamic compromise. Our goal was to characterize clinical and duplex parameters indicating patients at risk of recurrent ischemia. Methods-We retrospectively identified patients with symptomatic internal carotid artery occlusion. Clinical characteristics and ultrasound parameters, including collateral networks, were analyzed. Predictors for recurrent ipsilateral ischemia were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 20 publications
3
29
1
1
Order By: Relevance
“…5, 6, 36 However, unlike some prior studies, we did not see a difference in clinical outcome between MES+ and MES− patients. 2325 Currently, there are no surgical and few targeted therapeutic options for those with symptomatic carotid occlusion in contrast to carotid stenosis.…”
Section: Discussioncontrasting
confidence: 99%
“…5, 6, 36 However, unlike some prior studies, we did not see a difference in clinical outcome between MES+ and MES− patients. 2325 Currently, there are no surgical and few targeted therapeutic options for those with symptomatic carotid occlusion in contrast to carotid stenosis.…”
Section: Discussioncontrasting
confidence: 99%
“…The identification of the four main collateral pathways that can be assessed with TCD, was done as follows. 6,20,21 Here, for the number of possible collaterals we used the data for ACOM and PCOM from TOF MRA images, for ophthalmic artery the measured flow in Doppler TCD verified for presence of possible collateral since the ophthalmic artery identification in TOF MRA is due to anatomical conditions limited. 22 If no ophthalmic artery flow was measurable in TCD and no ophthalmic artery identifiable in TOF MRA, we counted as no anatomical possibility for ophthalmic collateral.…”
Section: Assessment Of Mr Angiographic Circle Of Willis Anatomy and Tcd Derived Collateral Circulation Pathwaysmentioning
confidence: 99%
“…Previous studies showed conflicting results regarding impact of secondary collaterals: while some studies linked the activation of secondary collaterals to impaired cerebral vasoreactivity, 11,21 others suggested that not the type but the number of activated collateral pathways indicates a higher risk of stroke recurrence in patients with carotid artery occlusion. 6,38,40 Connolly et al 41 assessed the activation of primary and secondary collaterals in patients with symptomatic ICA occlusion using TCD, and showed that ACOM collateral was most frequently activated, followed by ophthalmic, the PCOM and the leptomeningeal collaterals. In our cohort, likewise, ACOM collateral was most frequently activated followed by ophthalmic.…”
Section: Collateral Status Of Patients With Carotid Occlusionmentioning
confidence: 99%
See 1 more Smart Citation
“…По данным эпидемиологических исследований [2], симптоматические окклюзии ВСА ежегодно развиваются более чем у 6 на 100 000 населения, без учета пациентов, не обратившихся за специализированной помощью. Ультразвуковые исследования у больных с симптомами хронической церебральной ишемии выявляют каротидные окклюзии в 4% случаев [4].…”
unclassified